Enumeration of Legal Punishments Crimes in ImÄmiyya Criminal Law: Causes for Multiplicity of Opinions and the Necessity of Reckoning (Iá¸¥sÄâ) - Ã˜Â´Ã˜Â¹Ã˜Â¨Ã˜Â§Ã™Â†Ã›ÂŒ, Ã™Â…Ã™Â‡Ã˜Â¯Ã›ÂŒ; Ã™Â…Ã˜ÂÃ˜Â¨Ã˜Â§Ã™Â†, Ã™Â…Ã˜Â³Ã˜Â¹Ã™ÂˆÃ˜Â¯ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
Studying the nature of legal punishments (á¸¥udÅ«d) and legal misdemeanors deserving these kinds of punishment â which along with discretionary punishments (taâzÄ«rÄt) are regarded as the most important criminal reactions to crimes in Islamic criminal law system â despite their importance (both in terms of the intensity of punishment and the special favor that the religious law shows towards preserving the targets being threatened by these kinds of crimes) are still of concern and seem to be revisable. One of the outcomes of this theoretical discussion is that the ImÄmÄ« jurists have provided different readings and manifold opinions in determining the number and the titles of the causes of á¸¥udÅ«d. As its primary mandate, this research is intended to explore the scholastic reasons for this disagreement to figure out â after raising and analyzing the effective causes â whether the main source has finally been found to be in the opted viewpoint concerning the study of the nature of legal punishment crimes and their legal definition. Upon identifying the above-mentioned causes, it is to examine the important notion that the crimes deserving legal punishment (á¸¥add) are necessarily quantified (maá¸¥á¹£Å«r) and the list of these crimes are subject to scriptural ruling (tawqÄ«fÄ«) and are not increasable or reducible. It is attempted, in the present research, to prove the necessity to quantify the numerical range of the misdemeanors deserving legal punishment with reliance on a new definition consistent with the content of the legal texts of religious law that are implied from the legal nature of the above-mentioned crimes and by attesting to the general regulations and the legal restrictions placed on the process of criminalization. The argumentative approach of this article is trying to simultaneously provide the lexical meaning and the QurâÄnic-narrative concept of the word á¸¥add, as well as the fundamentalism and purposefulness in interpretation of texts and paying attention to the philosophy of legislating legal punishments (á¸¥udÅ«d). The new lawful changes in legal punishment crimes have also been critically and briefly analyzed in this research.